Goats (Capra hircus) From Different Selection Lines Differ in Their Behavioural Flexibility - Nawroth, Christian; Rosenberger, Katrina; Keil, Nina M.; Langbein, Jan (Frontiers in Psychology, 2022)
Given that domestication provided animals with more stable environmental conditions, artificial selection by humans has likely affected animals’ ability to learn novel contingencies and their ability to adapt to changing environments. In addition, the selection for specific traits in domestic animals might have an additional impact on subjects’ behavioural flexibility, but also their general learning performance, due to a re-allocation of resources towards parameters of productivity. To test whether animals bred for high productivity would experience a shift towards lower learning performance, we compared the performance of dwarf goats (not selected for production, 15 subjects) and dairy goats (selected for high milk yield, 18 subjects) in a visual discrimination learning and reversal learning task. Goats were tested individually in a test compartment and were rewarded by choosing either a white or a black cup presented by the experimenter on a sliding board behind a crate. Once they reached a designated learning criterion in the initial learning task, they were transferred to the reversal learning task. To increase the heterogeneity of our test sample, data was collected by two experimenters at two research stations following a similar protocol. Goats of both selection lines did not differ in the initial discrimination learning task in contrast to the subsequent reversal learning task. Dairy goats reached the learning criterion slower compared to dwarf goats (dairy goats = 9.18 sessions; dwarf goats = 7.74 sessions; P = 0.016). Our results may indicate that the selection for milk production might have affected behavioural flexibility in goats.